The effects of international email and Skype interactions on computer-mediated communication perceptions and attitudes and intercultural competence in Taiwanese students - Hsu, Shih-Yin Stella; Beasley, Robert E. (Australasian Journal of Educational Technology, 2019)
Learners in an English as a foreign language (EFL) context seldom have the opportunity to interact with people from other cultures and experience intercultural communication in English to foster their intercultural competence (IC), whether inside or outside of the classroom. In an effort to create a brand new opportunity to boost target language interactions, this study utilised two computer-mediated communication (CMC) tools, namely email and Skype, to involve Taiwanese EFL university students in an intercultural project to discuss interesting and cultural topics with university students from the USA. Data were collected from Taiwanese students’ reflective journals, a post-project questionnaire, and interviews. The study’s results indicate that despite encountering numerous problems initially, Taiwanese students eventually have strong positive perceptions and attitudes toward intercultural CMC learning experiences, which can facilitate efficient online discussions with native speakers of the target language and can promote IC. Thus, endeavours to implement such expedient, innovative, and beneficial methods in foreign language courses are encouraged.